ILRI communications getting social - MacMillan, Susan (International Livestock Research Institute, 2011)
Speaking at the January 2011 ILRI Partnerships and Communications (P&C) retreat, Susan MacMillan, Head of Public Awareness at ILRI reflects on the past year. She highlights that we moved from print to online; from normal media to social media, especially blogging. The big challenge for 2011: How are we going to continue, and take it up a notch? What I am most proud of last year: We made a major breakthrough in working as a team of web and communication specialists, using Yammer to share our updates and keep in contact.